The solubility of fluorite in Na-K-Cl solutions at temperatures up to 260 °C and ionic strengths up to 4 mol/kg H2O. (July 2017) - Zhang, Wei; Zhou, Li; Tang, Hongfeng; Li, Heping; Song, Wenlei; Xie, Gang
Abstract: The solubility of fluorite in hydrothermal conditions is important in ore forming and geothermal processes and groundwater utilization. However, a quantitative description of the geochemical behavior of fluorite under hydrothermal conditions has not been previously reported. In this work, the solubility of fluorite in Na-K-Cl solutions at temperatures up to 260 °C and ionic strengths up to 4 M was determined by experiments and modeling. The solubility products obtained in this work at 30 and 50 °C under ambient pressure and those from literature were used to regress the density model parameters for fluorite solubility product calculation at high temperature. The Pitzer interaction model was adopted to calculate the activity coefficient. The fluorite solubility determined in KCl solution at 250 °C under vapor saturated pressure and that from the literature were combined with the low-temperature thermodynamic properties of heat capacity and osmotic coefficient to obtain the binary parameters of NaF and KF at temperatures up to 260 °C. A thermodynamic model was then developed for calculating the fluorite solubility in Na-K-Cl solution at temperatures up to 260 °C, under vapor saturated pressure and ionic strengths up to 4 M. As calculated from this model, fluorite solubility measured at 200 °C and 0.1 M NaCl was well predicted. Both temperature and ionic strength had significant effects on fluorite solubility, and fluorite exhibited a similar dissolution pattern in both NaCl and KCl solution. When the concentration was lower than 2 M, the solubility of fluorite first increased with temperature, reached a maximum at approximately 100 °C, and then decreased. When the concentration was higher than 2 M, the solubility of fluorite increased monotonically with temperature. Highlights: The solubility product of fluorite can be calculated at temperatures up 260 °C. The binary Pitzer parameters of NaF and KF at temperatures up to 260 °C were obtained. Fluorite solubility can be calculated at temperatures up to 260 °C and ionic strengths up to 4 M in Na-K-Cl solution. Fluorite dissolution behavior affected by both temperature and ionic strength and is similar in NaCl and KCl solution.